Clinical spectrum of patients with posterior reversible encephalopathy syndrome - Pulavarty, Sriramchandra Rahul; Midathala, Nagabhushana (International Journal of Advances in Medicine, 2020)
Background: Posterior reversible encephalopathy syndrome is a neurological disorder which can present with sudden onset headache, visual disturbances, seizures and altered sensorium which is potentially reversible with early detection and treatment of the precipitating factor. The range of presentations is being constantly widened and this endeavour is a step towards understanding the wide array of presentation and primary etiology. Methods: This is a prospective observational study of 25 patients presenting to a tertiary care hospital with symptoms and imaging features suggestive of PRES. Thorough clinical examination and MRI brain were performed in all patients. Results: Out of the 25 patients, 18 (72%) were females and 7 (28%) were males. Most common symptom was headache (84%) followed by seizures (56%), nausea (40%), visual blurring (36%) and altered sensorium (20%). In patients presenting with seizure, 28.57% had recurrent seizures. The most common precipitating cause was postpartum state without hypertension (40%) followed by accelerated hypertension (28%), eclampsia (16%), chronic kidney disease (12%) and one patient of chronic severe anaemia had PRES following blood transfusion (4%). Most of the patients improved with no residual neurological deficit. Conclusions: Good neurological outcomes can be achieved by early diagnosis and appropriate imaging in patients with PRES. In pregnant and postpartum patients, PRES should be always considered even with normal blood pressure. Rapid correction of chronic severe anaemia is a rare but preventable cause of PRES.